Agama Djawa Sunda (ADS) - Roro Sri Rejeki Waluyajati (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2017)
The purpose of this article is to express the community about the existence of a indigenous religion whose existence nearly extinct. Indigenous religion is in known in the name of ADS (Religion Djawa Sunda). In expressing existence ADS and the use writers’ research methodology kulaitatif by using data analysis is inductive. Location for research in doing in Cigugur Village, district Kuningan. The result showed that Religion Djawa Sunda (ADS) is a religion local trying to combine between the sunda wiwitan and Islamic teachings.